Pengaruh Substitusi Tepung Tempe Terhadap Kadar Beta Karoten, Warna Dan Daya Terima Biskuit Ubi Jalar Ungu - Kusuma, Ayu Yahya; , Pramudya Kurnia, STP., M.Agr; , Endang Nur W, SST., M.Si Med (2016)
Purple sweet potato has a high content of beta carotene and can be processed into biscuits. Tempeh flour can be used as an ingredient in the manufacture of biscuits made from purple sweet potato to increase protein content. The use of purple sweet potato flour and tempeh flour can affect the chemical quality (beta carotene), physical quality (color) and sensory quality (acceptability) biscuits. The purposed of this study was to determine effect beta carotene content, colors and acceptability of purple sweet potato biscuits. The design of this study was completely randomized design with 4 treatments that is tempeh flour substitution is 0% (control), 10%, 15% and 20%. Levels of beta carotene were tested using the method of Thin Layer Chromatography (TLC) Densitometry, color tested using Chromameter Konica Minolta (CR-400) and acceptability of biscuits using organoleptic test by seven levels of hedonic scale. The statistical test was one-way ANOVA and if there is a significant influence (p≤0,05) followed by Duncan Multiple Range Test (DMRT) at significance level of 95%. The results showed that there was no difference in the levels of beta carotene on purple sweet potato biscuits substituted with tempeh flour. The test results showed that the color of tempeh flour substitution effect on the value of a, b and h0 but does not affect the value of L with significant value respectively p=0,000; p=0,001; p=0,000 and p=0,530. There was a significant substitution effect of tempeh flour to the acceptability of color, aroma, flavor, texture and overall purple sweet potato biscuits, with significant value respectively p=0.056; p=0.000; p=0.000; p=0.000; p=0.002. The conclusion of this study levels of beta carotene purple sweet potato biscuits substituted tempeh flour is <62,9mg/Kg. Based on acceptability and color, it is recommended to use of tempeh flour 10% of purple sweet potato biscuits.